Periodontal disease is associated with the risk of cardiovascular disease independent of sex: A meta-analysis - Leng, Yurong; Hu, Qinwen; Ling, Qin; Yao, Xiongda; Liu, Menglu; Chen, Jiawei; Yan, Zhiwei; Dai, Qun (Frontiers in Cardiovascular Medicine, 2023)
Objectives Studies have established a link between periodontal disease and cardiovascular disease (CVD), but it is unclear whether there is a sex difference in their association. Methods The PubMed, Embase, and Cochrane databases were searched until June, 21 2022. Cardiovascular outcomes included any CVD, myocardial infarction (MI), coronary heart disease (CHD), or stroke. Studies reported the prevalence of CVD in patients with periodontal disease and the relationship between periodontal disease and CVD. The study is registered with PROSPERO (CRD42022333663). The level of evidence and recommendations is assessed by the Grading of Recommendations for Assessment, Development and Evaluation (GRADE). Results Twenty-six studies were included. In patients with periodontal disease, the prevalence of CVD was 7.2% [9 studies; 95% confidence interval (CI): 2.7–13.6%], and prevalence for CHD, hypertension, stroke, and heart failure was 6.6, 25.3, 1, and 1.1%, respectively. There was a significant association between periodontal disease and CVD in men [odds ratio (OR) = 1.22; 95% CI: 1.12–1.34] and women (OR = 1.11; 95% CI: 1.05–1.17), with no significant sex difference (P > 0.05). Conclusion Cardiovascular disease is relatively common in patients with periodontal disease, and an increased risk of CVD is associated with periodontal disease independent of sex. Interventions targeting periodontal disease may be beneficial for CVD. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022333663.